Association of daily step counts and step intensity with mortality among US adults: a cross–sectional study of NHANES 2005–2006 - Tianzhou Peng; Changhao Liu; Ti Yang; Leyi Liao; Qingping Li; Hanbiao Liang; Jiapeng Zhang; Chen Xie; Kai Wang; Chuanjiang Li (BMC Gastroenterology)
Abstract Background & aims We aimed to describe the dose–response relationship between daily step counts and intensity with respect to all–cause mortality among US adults diagnosed with metabolic dysfunction–associated steatotic liver disease (MASLD). Methods Using data from the National Health and Nutrition Examination Survey (NHANES) database spanning from 2005 to 2006, a cross–sectional study included 1,108 participants was performed to assess the relationship between daily step counts and step intensity with mortality. Results A total of 1,108 participants from the NHANES study were included, with a mean age of 49.5 ± 0.9 years. The sample consisted of 533 (48.1%) women, 809(73%) non–Hispanic whites, 122 (10.8%) non–Hispanic blacks, 133 (12.0%) Hispanic, and 44 (4.2%) individuals of other racial backgrounds. Using multivariable–adjusted Cox proportional hazards models, we found that compared to participants in the light–step group, there was significantly lower risk of mortality in the moderate (hazard ratio [HR], 0.47 [95% CI, 0.32–0.69]), high (HR, 0.35 [95% CI, 0.21–0.61]) and vigorous (HR,0.45 [95% CI, 0.22–0.93]) step groups. Sensitivity and subgroup analyses confirmed that the association between step count and mortality remained robust. However, after adjusting for all covariates, greater step intensity was not significantly associated with lower mortality. Further analysis revealed that age, BMI, and self–rated health could have confounded the relationship between step intensity and survival, potentially obscuring any direct effect of step intensity on mortality. Conclusions Accumulating a higher number of daily steps, rather than focusing on step intensity, was associated with a lower risk of all–cause mortality in individuals with MASLD. Our findings suggest that achieving 10,000 steps per day may be optimal for reducing the risk of all–cause mortality risk in this population.